Pelaksanaan Perlindungan Kesehatan dan Keselamatan Kerja Terhadap Pekerja Perseroan Terbatas - Jalu Ario Setyo Utomo; Lego Karjoko (Jurnal Discretie, 2020)
This research is come from the importance of human resources in doing work. The factor that easily affects human resources in terms of production is Occupational Health and Safety (K3). Factors that influence the implementation of Occupational Safety and Health (K3) at PT. Halo Indonesia Manufacture, namely personal protective equipment (PPE), warning signs, human resources (HR) and technology.  The implementation of Occupational Safety and Health (K3) at PT. Halo Indonesia Manufacture, namely establishing an Occupational Safety and Health Management System (SMK3), preventing and reducing accidents, extinguishing fires, providing aid in accidents, providing personal protective equipment to employees and providing training on work safety.